Improve Communication Skills with Interpersonal Students Through Counseling Group With Narrative Approach - Supraptini, Supraptini (International Journal of Applied Guidance and Counseling, 2023)
Communication is an interaction process that is an individual's effort to be actively involved in life. Interpersonal communication boils down to personal abilities in interacting with their environment so that individuals can carry out all their activities smoothly in the situations they face. The purpose of this research was to help students have interpersonal communication skills so that they have personal qualities that can interact and adapt to the environment. The method in this action research uses a narrative counseling approach, which is an approach that is suitable for use in services that help with problems related to interpersonal communication. Narrative counseling focuses on directing the client to public speaking, which is the ability to adapt in interactions. The process of a narrative counseling approach in helping problems is carried out using the client telling what is experienced in his personal life, where the activeness of the counselor as a facilitator and the activeness of the counselee is to convey stories as experiences in his life. The use of this narrative counseling approach is based on a conceptual framework to assist clients in finding new meanings and new possibilities in their lives. The narrative counseling approach helps improve interpersonal communication skills by obtaining success of 92%, and there are 23.25% contributing to an increase from the previous percentage, namely 68.75%. These data show that the narrative counseling approach is one of the various approaches that can be used in group Guidance and Counseling services in schools. Guidance and Counseling services have an important and strategic role in supporting the achievement of educational goals holistically.